Ligand-free few atoms Ag nanoclusters synthesis and their potential application as photocatalytic agents - Santillán, Jesica María José (2020)
We have implemented ultrafast laser ablation synthesis in liquids together with mechanical centrifugation to obtain ligand-free silver nanoclusters (Ag NCs). Given the nature of this technique, the NCs colloids produced are highly pure which avoids additional cleaning protocols. The mechanical centrifugation of the colloids helps to separate the NCs from their larger counterparts (nanoparticles (NPs)), present in the suspension. Synthesized NC colloids are studied by fluorescence spectroscopy observing UV bands corresponding with HOMO-LUMO cluster transitions, and HRTEM measurements where Ag NCs clouds and Ag atomic clusters are observed. Finally, the photocatalytic response of the Ag NCs was studied by the degradation of the standard molecule Methylene Blue (MB) in interaction with white light. It was observed that when MB and Ag NCs are mixed in the solution, degradation of MB is much faster, indicating the strong photocatalytic response of NCs, even at low concentrations.